Frontotemporal dementia spectrum: first genetic screen in a Greek cohort - Ramos,E.M.; Koros,C.; Dokuru,D.R.; Van,Berlo,V; Kroupis, C.; Wojta,K.; Wang,Q.; Andronas,N.; Matsi,S.; Beratis,I.N.; Huang,A.Y.; Lee,S.E.; et al. (Neurobiol.Aging, 2019)
Frontotemporal dementia (FTD) is a heterogeneous group of neurodegenerative syndromes associated with several causative and susceptibility genes. Herein, we aimed to determine the incidence of the most common causative dementia genes in a cohort of 118 unrelated Greek FTD spectrum patients. We also screened for novel possible disease-associated variants in additional 21 genes associated with FTD or amyotrophic lateral sclerosis. Pathogenic or likely pathogenic variants were identified in 16 cases (13.6%). These included repeat expansions in C9orf72 and loss-of-function GRN variants, and likely pathogenic variants in TARDBP, MAPT, and PSEN1. We also identified 14 variants of unknown significance in other rarer FTD or amyotrophic lateral sclerosis genes that require further segregation and functional analysis. Our genetic screen revealed a high genetic burden in familial Greek FTD cases (30.4%), whereas only two of the sporadic cases (3.5%) carried a likely pathogenic variant. A substantial number of familial cases still remain without an obvious causal variant, suggesting the existence of other FTD genetic causes besides those currently screened in clinical routine
Keywords: Amyotrophic Lateral Sclerosis; analysis; Asian People; C9orf72 Protein; Cohort Studies; DNA Repeat Expansion; Female; Frontotemporal Dementia; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; genetics; Greece; Humans; Male; Mutation